PLANNED BEHAVIOR THEORY IN PAYING CASH WAQF - Putra, Purnama; ., Isfandayani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The potential of Waqf in Indonesia which is in the movement of followers of the largest Muslim religion in the World that is equal to 85% since the days of Pre-Independence. The legal order in Indonesia that underlies the management of waqf is very complete than Zakat, Infaq or Alms. This completeness is manifested in Law No. 41/2004 concerning Endowments and Government Regulation No. 42/2006 concerning Implementation of Law No. 41/2004. Both legality in the form of regulations and the Law provide a more certain legal basis for increasing public trust and guarantee of waqf assets. It became the starting point for the management of waqf and the collection of waqf funds in Indonesia. This study uses a quantitative method design in identifying what factors influence people's intentions in carrying out cash waqf. Data collection is done through filling out the questionnaire then be processed the validity and reliability test of 50 people and then given to a sample of 200 people. Factors affecting the intention to fulfill cash waqf based on this research are Attitude, Subjective Norms and Behavioral Control. Third, the Attitude, Subjective Norm, and Behavioral Control variables together have a significant influence on the variables of waqf intentions on cash waqf. Attitude variable towards cash Intention variable is 4.62%, Subjective Norm variable is 2.88%, Behavioural Control variable is 8.5%. Therefore, it can be concluded that the most dominant effective contribution value influencing cash intention variable is the Behavioral Control variable that is 8.5%.